(untitled) (UUM Journal of Legal Studies, 2020)
The Fourth Industrial Revolution (IR 4.0) has undeniably affected the way of life of people, including children. The rapid development of the internet and digital technology coupled with unlimited, easy, and fast access make children highly susceptible to harm arising from the use of social media, films, or games. This situation may expose children who are beyond control to immense threats due to poor relationships with their parents and family members. The beyond control children may be found anywhere. They are the children who frequently disobey their parentsâ€™ orders and are notorious as â€œstatus offendersâ€ at the international level. Despite the non-criminal nature of their misbehaviour, children who are beyond control are often treated like criminals through court proceedings and detention orders. Meanwhile, numerous international conventions and guidelines have been signed including the United Nations Convention on the Rights of the Child to protect the welfare of all children. However, to what extent do these conventions protect the children who are beyond control? What are the principles applicable to these children, and how are they protected? Thus, this study was done to analyse the extent of protection provided by international conventions for the rights of children who are beyond control and to suggest suitable programmes for the implementation of the international principles in the IR 4.0 era. This qualitative study employed the library research method for data collection. It analysed numerous documents including international conventions, statutes, books, journals, conference proceedings, and reports. This study found that the international conventions provide protection to the children who are beyond control through several principles including the best interest of the child, family and government responsibilities, institutional placement, prevention of delinquency, and diversion. These principles may be applied through diversionary programmes including counselling, family group conference, family and school programme, and mentoring programme.